ANALISIS MINAT BELAJAR SISWA KELAS 3 SDIT RAUDHATURRAHMAH DALAM MENGIKUTI PEMBELAJARAN TATAP MUKA TERBATAS - Yuwono, Tristiyo Hendro; Lestari, Reni Dian; Putra, M. Jaya Adi (STKIP Pesisir Selatan, 2022)
This study aims to analyze the Learning Interest of Class 3 Ar-Rahman SDIT Raudhaturrahmah Students in Participating in Limited Face-to-Face Learning, aims to determine the categories of students' interest in learning in participating in learning. This research is a qualitative descriptive study. Data collection techniques in this study are observation and interviews. The stages in this research are: Selecting the problem, collecting the relevant, collecting data, selecting the data, and analyzing the data. Based on the research that has been done by the researcher, it can be concluded from the results of interviews and observations of students' interest in participating in Class 3 Learning at SDIT Raudhaturrahmah with limited face-to-face learning in good category